2004
DOI: 10.2133/dmpk.19.245
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Prevention by Natural Compounds

Abstract: Increasing attention is being paid to the possibility of applying cancer chemopreventive agents for individuals at high risk of neoplastic development. For this purpose by natural compounds have practical advantages with regard to availability, suitability for oral application, regulatory approval and mechanisms of action. Candidate substances such as phytochemicals present in foods and their derivatives have been identified by a combination of epidemiological and experimental studies. Plant constituents inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
115
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(121 citation statements)
references
References 127 publications
2
115
0
4
Order By: Relevance
“…The development of drugs that specifically target tumor cells, but not normal cells, represents a common goal. Natural compounds contain various types of medicinal ingredients, including vitamin derivatives, phenolic and flavonoid agents, organic sulfur compounds, isothiocyanates, curcumins, fatty acids and D-limonene (Amin et al, 2009;Gullett et al, 2010;Tsuda et al, 2004), and sufficient evidences have demonstrated that these components can substantially inhibit tumor formation (Amin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The development of drugs that specifically target tumor cells, but not normal cells, represents a common goal. Natural compounds contain various types of medicinal ingredients, including vitamin derivatives, phenolic and flavonoid agents, organic sulfur compounds, isothiocyanates, curcumins, fatty acids and D-limonene (Amin et al, 2009;Gullett et al, 2010;Tsuda et al, 2004), and sufficient evidences have demonstrated that these components can substantially inhibit tumor formation (Amin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These electrophiles commonly conjugate with glutathione by glutathione S-transferase, which prevents them from forming DNA adducts. Some publications have reported that the induction of glutathione S-transferase activity is correlated with cancer prevention (Puatanachokchai et al, 2002;Tsuda et al, 2004). Our previous studies also showed that S neglecta enhanced some hepatic antioxidant enzymes in rats (Thumvijit et al, 2013b).…”
Section: Discussionmentioning
confidence: 63%
“…Flavonoids act as general cell growth inhibitors and apoptosis inducers, which makes them prime candidates in the development of new anticancer compounds (27)(28)(29). Also, several studies have shown that flavonoids are protective against DMBA-induced rat mammary tumorigenesis (30,31).…”
Section: Discussionmentioning
confidence: 99%